Redox Stress Response and Uv Tolerance in the Acidophilic Iron-Oxidizing Bacteria Leptospirillum Ferriphilum and Acidithiobacillus Ferrooxidans - Levican-Jaque, G; Chavez-Rosales, R; Farías-Oyarce, R (Elsevier Masson s.r.l., 2021)
The oxidative stress response represents a sum of antioxidative mechanisms that are essential for determining the adaptation and abundance of microorganisms in the environment. Leptospirillum ferriphilum and Acidithiobacillus ferrooxidans are chemolithotrophic bacteria that obtain their energy from the oxidation of ferrous ion. Both microorganisms are important for bioleaching of sulfidic ores and both are tolerant to high levels of heavy metals and other factors that can induce oxidative stress. In this work, we compared the tolerance and response of L. ferriphilum and At. ferrooxidans to Fe3+, H2O2, K2CrO4, and UV-C radiation. We evaluated growth, generation of reactive oxygen species (ROS), oxidative damage to lipid membranes and DNA, and the activity of antioxidative proteins in cells exposed to these stressors. L. ferriphilum had higher cell density, lower ROS content and less lipid and DNA damage than At. ferrooxidans. Consistent with this, the activity levels of thioredoxin and superoxide dismutase in L. ferriphilum were upregulated and higher than in At. ferrooxidans. This indicated that L. ferriphilum has a higher capacity to respond to oxidative stress and to manage redox homeostasis. This capacity could largely contribute to the high abundance of this species in natural and anthropogenic sites. © 2021 Institut Pasteur